Stochastic analysis of delayed reporting of faults in a computer network using copula distribution. (14th June 2023) - Poonia, Praveen Kumar; Singh, Vijay Vir
The objective of this paper is to study the system reliability of a computer network incorporating delayed reporting of non-fatal faults. We divided the network into four subsystems that includes router, gateway switch, two identical load balancers, and n similar application or web servers working under k-out-of-n: G policy with standby arrangement and all are connected in series. This mathematical model uses a significant feature of load balancing combining delayed reporting of non-fatal faults in a computer network under catastrophic failure by assuming two different forms of failure between neighbouring transitions from which the designed system's behavioural analysis can be examined. The paper aims to find various reliability characteristics using supplementary variable technique and Laplace transformation with the implications of Gumbel-Hougaard family of copula distribution. The study shows a significant improvement in availability and expected cost while we ensured with the use of copula repair.